Analisis Kepatuhan Wajib Pajak Orang Pribadi Terhadap Penerimaan Pajak Penghasilan (PPh) Pasal 21 Pada KPP Pratama Tebing Tinggi - Arfah, Yenni; Sari, Devi Novita; Panjaitan, Dwi Fany Azra (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2025)
This study aims to analyze the compliance level of individual taxpayers with regard to the income tax revenue from Article 21 at the Pratama Tax Office (KPP Pratama) in Tebing Tinggi. A qualitative descriptive approach was adopted, utilizing primary data through interviews with tax officers and secondary data from reports and relevant literature. The findings show a decreasing trend in compliance from 77.97% in 2021 to 57.7% in 2023, despite a steady increase in registered taxpayers. This indicates that a larger taxpayer base does not necessarily lead to higher compliance. The main contributing factors to low compliance include insufficient knowledge of tax obligations, lack of awareness about filing procedures, and misperceptions regarding the tax system. Although the tax revenue from Article 21 remained relatively high—exceeding targets in 2021 and 2022 and nearing the target in 2023—this was primarily driven by high-income taxpayers subject to progressive tax rates. The results demonstrate that tax revenue performance is not solely dependent on overall taxpayer compliance levels. This study highlights the need for targeted taxpayer education, service improvement, and a localized strategy to address behavioral gaps in the self-assessment tax system.